2004
DOI: 10.1146/annurev.biochem.73.071403.161303
|View full text |Cite
|
Sign up to set email alerts
|

Inositol 1,4,5-Trisphosphate Receptors as Signal Integrators

Abstract: The inositol 1,4,5 trisphosphate (IP3) receptor (IP3R) is a Ca2+ release channel that responds to the second messenger IP3. Exquisite modulation of intracellular Ca2+ release via IP3Rs is achieved by the ability of IP3R to integrate signals from numerous small molecules and proteins including nucleotides, kinases, and phosphatases, as well as nonenzyme proteins. Because the ion conduction pore composes only approximately 5% of the IP3R, the great bulk of this large protein contains recognition sites for these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
422
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 412 publications
(427 citation statements)
references
References 179 publications
3
422
0
2
Order By: Relevance
“…This effect of ouabain is most likely due to the activation of Src. First, prior studies showed that Src family kinases could phosphorylate IP3R1 isoform (Jayaraman et al, 1996;Yokoyama et al, 2002;Cui et al, 2004;Patterson et al, 2004). Second, inhibition of Src abolished ouabain-induced tyrosine phosphorylation of the receptor (Figure 7).…”
Section: Regulation Of Plc-␥1 and Ip3r2 By The Activated Na/katpase Smentioning
confidence: 83%
See 1 more Smart Citation
“…This effect of ouabain is most likely due to the activation of Src. First, prior studies showed that Src family kinases could phosphorylate IP3R1 isoform (Jayaraman et al, 1996;Yokoyama et al, 2002;Cui et al, 2004;Patterson et al, 2004). Second, inhibition of Src abolished ouabain-induced tyrosine phosphorylation of the receptor (Figure 7).…”
Section: Regulation Of Plc-␥1 and Ip3r2 By The Activated Na/katpase Smentioning
confidence: 83%
“…Because the activated PLC-␥1 produces the ligand (IP3) of IP3 receptors, we tested whether the ouabain-activated complex could also recruit IP3 receptors in LLC-PK1 cells. Furthermore, we also tested whether the same ouabain-activated complex stimulates the tyrosine phosphorylation of IP3 receptors because Src family kinases can phosphorylate these receptors, resulting in increased sensitivity to IP3 (Jayaraman et al, 1996;Yokoyama et al, 2002;Cui et al, 2004;Patterson et al, 2004). As depicted in Figure 6A, we identified all three isoforms of IP3 receptors from LLC-PK1 cell lysates with commercially available antibodies.…”
Section: Ouabain-activated Na/k-atpase Signaling Complex Interacts Wimentioning
confidence: 99%
“…Several processes contribute to the spatial and temporal dynamics of Ca 2+ , such as diffusion and buffering, exchange with the extracellular space, and uptake and release from intracellular stores. The inositol 1,4,5-trisphosphate receptor (IP 3 R) ion channel is a key component in shaping Ca 2+ signals, as it controls the local efflux from the endoplasmic reticulum (ER), where Ca 2+ is sequestered at high concentration (5,6). The IP 3 R is a ligand-gated channel, subject to regulation by binding of IP 3 and also Ca 2+ itself.…”
mentioning
confidence: 99%
“…It has been reported that the short distance between Cys160 and Cys212 in domain b suggests a strong potential to form a covalent linkage and is likely to be present in vivo (Patterson et al, 2004). The disulphide bond of ERp44 may be important for inhibition of IP 3 Rs activity by blocking free thiol groups in the L3V domain of IP 3 Rs (Higo et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…There are two major types of intracellular calcium release channels or receptors, rynaodine receptors (RyRs) and inositol 1,4,5-trisphosphate receptors (IP 3 Rs), located on sarcoplasmic reticulum (SR) or ER and nuclear membrane. Upon binding to IP 3 , IP 3 Rs release Ca 2+ to integrate signals from numerous small molecules and proteins and modulate diverse cellular functions (Patterson et al, 2004).…”
Section: Introductionmentioning
confidence: 99%